Problem based-learning supported flipped classroom approach to enhance collaborative skills - Gunawan, Tri (JIPSINDO, 2023)
Collaboration skills, which are one of the core 21st-century competencies, have not been optimally observed in class X-7 of SMA Negeri 1 Kasihan. Therefore, the implementation of problem-based learning supported by the Flipped Classroom approach is necessary. The objective of this research is to analyze the improvement of collaboration skills after the implementation of problem-based learning supported by the Flipped Classroom approach in class X-7 of SMA Negeri 1 Kasihan. This research is conducted in two cycles as a classroom action research. Data collection is carried out through direct observation during learning activities and distribution of questionnaires to the students to obtain their perspectives on the learning experience. The collected data is then analyzed using descriptive quantitative analysis. In the first cycle, the research results showed that the average collaboration skills of the students were 67.04 with a classical completeness level of 67.04%. This indicates that the implementation of problem-based learning with the Flipped Classroom approach in the first cycle has led to an improvement in students' collaboration skills. However, there is still room for improvement. Furthermore, in the second cycle, there was a significant increase in students' collaboration skills. The average score for collaboration skills increased to 75.46 with a classical completeness level of 75.46%. It can be observed that there was an improvement of 8.42 in the average collaboration skills and a similar increase in the classical completeness level between the first and second cycles. Based on the results of this research, it can be concluded that the implementation of problem-based learning supported by the Flipped Classroom approach is effective in improving students' collaboration skills.Pembelajaran berbasis masalah dengan kelas terbalik untuk memperkuat  kerjasama Keterampilan berkolaborasi yang merupakan salah satu kompetensi inti abad 21 belum terlaksana secara optimal di kelas X-7 SMA Negeri 1 Kasihan. Oleh karena itu, penerapan pembelajaran berbasis masalah yang didukung dengan pendekatan Flipped Classroom sangat diperlukan. Tujuan penelitian ini adalah untuk menganalisis peningkatan keterampilan kolaborasi setelah penerapan pembelajaran berbasis masalah dengan dukungan pendekatan Flipped Classroom pada kelas X-7 SMA Negeri 1 Kasihan. Penelitian ini dilaksanakan dalam dua siklus sebagai penelitian tindakan kelas. Pengumpulan data dilakukan melalui observasi langsung selama kegiatan pembelajaran dan penyebaran angket kepada siswa untuk memperoleh pandangan mereka terhadap pengalaman belajar. Data yang terkumpul kemudian dianalisis dengan menggunakan analisis deskriptif kuantitatif. Pada siklus I hasil penelitian menunjukkan rata-rata keterampilan kolaborasi siswa sebesar 67,04 dengan tingkat ketuntasan klasikal sebesar 67,04%. Hal ini menunjukkan bahwa pelaksanaan pembelajaran berbasis masalah dengan pendekatan Flipped Classroom pada siklus I telah menyebabkan peningkatan keterampilan kolaborasi siswa. Namun, masih ada ruang untuk perbaikan. Selanjutnya pada siklus II terjadi peningkatan yang signifikan pada keterampilan kolaborasi siswa. Nilai rata-rata keterampilan kolaborasi meningkat menjadi 75,46 dengan tingkat ketuntasan klasikal 75,46%. Terlihat adanya peningkatan rata-rata keterampilan kolaborasi sebesar 8,42 dan peningkatan serupa pada tingkat ketuntasan klasikal antara siklus I dan II. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan pembelajaran berbasis masalah yang didukung pendekatan Flipped Classroom efektif dalam meningkatkan keterampilan kolaborasi siswa.